Method and device for modifying graphite felt electrode of flow battery

By using chemical reagents such as KF, NaCl, KClO3 and NH3HF in all vanadium liquid flow batteries to calcin and modify the graphite felt electrode, the problem of poor aging stability of electrode activity was solved, and the electrochemical activity and reaction stability was improved.

CN119560570APending Publication Date: 2025-03-04CHINA NAT PETROLEUM CORP +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311128013.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-01
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The current graphite felt electrodes in all vanadium liquid flow batteries have poor electrochemical activity and aging stability, resulting in slow battery reaction rate, poor redox reversibility, high reaction polarization degree, and low electrolyte utilization rate.

Method used

By mixing and grinding the initial powder under a dry environment, reagents providing an oxygen source and nitrogen source are added to form a third mixed powder, covering the graphite felt electrode and calcined modification. This method uses chemical reagents such as KF, NaCl, KClO3 and NH3HF to achieve etching of the fiber surface and doping of N/O through one calcination.

Benefits of technology

The multifunctional modification of graphite felt electrodes is realized, the electrochemical activity and reaction stability of the electrodes are improved, the etching effect is enhanced, the modification cost is reduced, and the process flow is simplified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560570A_ABST
    Figure CN119560570A_ABST
Patent Text Reader

Abstract

The invention discloses a flow battery graphite felt electrode modification method which comprises the following steps: fully mixing and grinding initial powder in a dry environment to obtain first mixed powder; adding a reagent for providing an oxygen source into the first mixed powder in batches, and stirring in a dry environment to obtain second mixed powder; adding a reagent for providing a nitrogen source into the second mixed powder in batches, and stirring in a dry environment to obtain third mixed powder; a graphite felt electrode is covered with the third mixed powder for calcination modification. The modification process and the operation process are simple, and modification can be completed only by preparing the mixed etching powder and then calcining the mixed etching powder. In addition, the modification cost is lower, and chemical reagents, conventional experimental equipment and the like which are low in price are used. Meanwhile, the method is skillful in that the selected O source and N source are strong etching agents, so that the etching effect is remarkably enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of graphite felt electrode modification, and in particular to a method and a device for modifying a graphite felt electrode of a flow battery. Background Art

[0002] Electrochemical energy storage has become the main development direction of current energy storage technology due to its flexible application scenarios, excellent storage and discharge performance, and fast system response. However, the current lithium-ion battery has a short energy storage time, and the lack of key raw material reserves has led to high costs, making it difficult to meet the long-term energy storage needs of large-scale power stations. All-vanadium liquid flow batteries have the advantages of large capacity, high safety, long service life, and flexible structure, and have shown great application prospects in energy storage, smart grids, emergency power supplies, and new energy vehicles.

[0003] All-vanadium liquid flow battery is mainly composed of flow channel frame, electrode, diaphragm, liquid storage tank, pump and electrolyte. The active materials of positive and negative electrolyte are VO 2+ / VO 2+ and V 3+ / V 2+ The electrolyte circulates through the pump to produce a redox reaction on the electrode surface. The positive and negative electrodes pass through the diaphragm (only H + When the battery is charged, the positive electrode VO 2+ Lose electrons to form VO 2+ , negative electrode V 3+ Electrons are obtained to form V 2+ The discharge process is the opposite, and the battery conducts electricity through H+ migration. The electrode is the main place for the battery to provide electrochemical reactions. The choice of electrode will greatly affect the battery performance. The research, development and utilization of electrode materials are crucial to the early large-scale commercial application of vanadium batteries.

[0004] Carbon materials are common materials for vanadium battery electrodes, including carbon cloth, graphite plate, carbon felt, flexible graphite composite plate, and carbon paper. In terms of physical properties, carbon materials generally have good conductivity and are suitable for electrode materials. In terms of chemical properties, carbon materials have good corrosion resistance and are suitable for various complex environments. Therefore, in the selection of flow battery electrodes, carbon material graphite felt is given priority both at home and abroad.

[0005] Graphite felt is the product of carbon felt treated at a high temperature of more than 2000 degrees Celsius in an inert atmosphere or in a vacuum. It is made by mixing graphite and polymer materials, and contains up to 99% carbon. The original graphite felt has poor wettability. Poor wettability will reduce the number of active sites for ion reaction provided by the electrode, and the contact surface area between the electrode and the electrolytic solution will also be reduced, resulting in poor electrochemical performance of the electrode. Therefore, the original graphite felt must be modified to improve its performance. Summary of the invention

[0006] The purpose of the present invention is to provide a method and device for modifying graphite felt electrodes of a liquid flow battery to solve the above-mentioned technical problems.

[0007] To achieve the above object, the present invention provides a method for modifying a graphite felt electrode of a flow battery, comprising:

[0008] Fully mixing and grinding the initial powders in a dry environment to obtain a first mixed powder;

[0009] Adding a reagent providing an oxygen source to the first mixed powder in batches, and obtaining a second mixed powder by stirring in a dry environment;

[0010] Adding a nitrogen source providing reagent to the second mixed powder in batches, and obtaining a third mixed powder by stirring under a dry environment;

[0011] Covering the graphite felt electrode with the third mixed powder for calcination modification;

[0012] The initial powder includes at least two of the following: KF, NaCl, KCl, NaF, KBr and NaBr.

[0013] Optionally, the initial powder is KF and NaCl; wherein the mass ratio of the KF to the NaCl is 1:1 to 1.5:1.

[0014] Optionally, the mixing and grinding time is 5-10 minutes.

[0015] Optionally, the reagent providing an oxygen source includes at least one of the following: KClO4, KClO3, KClO2, KBrO3, KBrO2, NaClO4, NaClO3, NaClO2, NaBrO3 and NaBrO; the reagent providing a nitrogen source includes at least one of the following: NH3HF, NH4Cl and NH4Br.

[0016] Optionally, the reagent providing the oxygen source is KClO3; wherein the mass of the KClO3 added is 2-15% of the total mass of the KF and the NaCl.

[0017] Optionally, the reagent providing the nitrogen source is NH3HF; wherein the mass of the added NH3HF is 0.8-8% of the total mass of the KF, the NaCl and the KClO3.

[0018] Optionally, the third mixed powder is used to cover the graphite felt electrode for calcination modification, comprising:

[0019] Placing a graphite felt electrode in a crucible, and evenly covering the third mixed powder with the graphite felt on all sides;

[0020] The crucible is transferred to a vertical molten salt furnace under an Ar atmosphere for calcination;

[0021] Wherein, the thickness of the covering is 1-1.5 cm.

[0022] Optionally, the calcination conditions include: calcination temperature 200-350°C, calcination time 2-3h, heating rate 3-5°C·min -1 .

[0023] Optionally, the method further includes:

[0024] The modified graphite felt electrode was removed from the crucible and rinsed repeatedly with deionized water;

[0025] The rinsed graphite felt electrode was placed in a vacuum drying oven for drying.

[0026] The present invention also provides a device for modifying graphite felt electrodes of a flow battery, comprising:

[0027] A first obtaining unit is used to fully mix and grind the initial powder in a dry environment to obtain a first mixed powder;

[0028] A second obtaining unit is used to add a reagent providing an oxygen source to the first mixed powder in batches, and obtain a second mixed powder by stirring in a dry environment;

[0029] A third obtaining unit is used to add a reagent providing a nitrogen source to the second mixed powder in batches, and obtain a third mixed powder by stirring in a dry environment;

[0030] A calcination unit is used for calcining and modifying the graphite felt electrode by covering it with the third mixed powder.

[0031] Technical effects and advantages of the present invention:

[0032] There are many types of modification technologies for graphite felt electrodes of all-vanadium liquid flow batteries, which often have the disadvantages of complex processing technology, cumbersome operation process, high modification cost, and often use a large amount of chemical reagents to pollute the environment. At the same time, the electrochemical activity and aging stability of the graphite felt electrodes modified by traditional single measures are poor. In contrast, the advantages of the present invention are:

[0033] 1. The modification process and operation flow are simple. In the present invention, only the mixed etching powder is prepared and then calcined to complete the modification. 2. The present invention adds fewer types of chemical reagents, and only four chemical reagents, KF, NaCl, KClO3 and NH3HF, are used. 3. The modification cost of the present invention is lower, and all used are low-priced chemical reagents and conventional experimental equipment. 4. The multifunctional modification of the graphite felt electrode is realized. KF and NaCl provide a highly thermally stable molten salt environment, and O source KClO3 and N source NH3HF are added respectively. The four chemical reagents are mixed and calcined once to simultaneously achieve the etching of the fiber surface and the doping of N / O. 5. The ingenuity of the present invention is that the selected O source and N source are both strong etchants, which significantly enhances the etching effect.

[0034] Other features and advantages of the present invention will be described in the following description, and partly become obvious from the description, or be understood by implementing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The present invention is a flow chart of the modification method of graphite felt electrode for flow battery;

[0036] Figure 2 The SEM images of GF modified with different process parameters in implementation case 1 (a), implementation case 2 (b) and implementation case 3 (c);

[0037] Figure 3 The CON element distribution diagrams on the surface of unmodified GF (a), (b), (c) and modified GF fiber of implementation case 3 (d), (e), (f);

[0038] Figure 4 The cyclic voltammetry curves of unmodified GF and modified GF in Example 3 are shown in FIG.

[0039] Figure 5 The bar graphs of charge and discharge energy density of unmodified GF and modified GF at different current densities;

[0040] Figure 6 The charge and discharge voltage curves of the unmodified GF and the modified GF in Example 3 are shown. DETAILED DESCRIPTION

[0041] The technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings provided by the present invention, and the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0042] It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification for people familiar with this technology to understand and read, and are not used to limit the limiting conditions for the implementation of the present invention, so they have no substantial technical significance. Any modification of the structure, change of the proportion relationship or adjustment of the size should still fall within the scope of the technical content disclosed by the present invention without affecting the effects and purposes that can be achieved by the present invention. At the same time, the terms such as "upper", "lower", "left", "right", "middle" and "one" quoted in this specification are only for the convenience of description, and are not used to limit the scope of the implementation of the present invention. The change or adjustment of their relative relationship should also be regarded as the scope of the implementation of the present invention without substantially changing the technical content.

[0043] Graphite felt electrodes, which are widely studied and applied in all-vanadium liquid flow batteries, have advantages such as high porosity three-dimensional structure, high conductivity, excellent mechanical properties and good chemical stability. Their performance seriously affects the comprehensive energy storage performance and application cost of liquid flow batteries. However, the unmodified graphite felt electrodes have low electrocatalytic activity for vanadium ions of different valence states, poor electrode surface wettability, and small electrochemical specific surface area, resulting in slow electrode reaction rate, poor redox reversibility, high reaction polarization degree, and low electrolyte utilization, making it difficult for the battery to obtain excellent power storage cycle performance.

[0044] In order to solve the above problems, the present invention discloses a method for modifying a graphite felt electrode of a flow battery, such as Figure 1 The method comprises:

[0045] 1. The initial powders are fully mixed and ground in a dry environment to obtain a first mixed powder.

[0046] The initial powder includes at least two of the following: KF, NaCl, KCl, NaF, KBr and NaBr. Preferably, the present invention uses KF and NaCl. KF and NaCl are both analytically pure, and the mass ratio of KF to NaCl is 1:1 to 1.5:1; KF and NaCl molten salts need to be kept dry.

[0047] 2. Adding a reagent providing an oxygen source to the first mixed powder in batches, and obtaining a second mixed powder by stirring in a dry environment.

[0048] The reagent providing the oxygen source is both an etchant and an O source, and includes at least one of the following: KClO4, KClO3, KClO2, KBrO3, KBrO2, NaClO4, NaClO3, NaClO2, NaBrO3 and NaBrO. Preferably, the present invention selects KClO3 as an etchant and an O source (decomposed into O2 at 400°C). The mass of the added KClO3 is 2-15% of the total mass of the KF and the NaCl; after the KF, NaCl and KClO3 are fully mixed, they shall not be ground and shall be kept dry.

[0049] 3. Adding a nitrogen source providing reagent to the second mixed powder in batches, and obtaining a third mixed powder by stirring in a dry environment.

[0050] The reagent providing the nitrogen source is both an etchant and a N source, and includes at least one of the following: NH3HF, NH4Cl and NH4Br. Preferably, the present invention selects NH3HF as an etchant and a N source (decomposed into NH3 at 200°C). The mass of the added NH3HF is 0.8-8% of the total mass of the KF, the NaCl and the KClO3; NH3HF is added to KF, NaCl and KClO3 in batches without grinding, and is stirred evenly; NH3HF is added to KF, NaCl and KClO3, and then fully mixed and kept dry.

[0051] 4. Covering the graphite felt electrode with the third mixed powder for calcination modification.

[0052] Specifically, the third mixed powder is evenly covered with graphite felt on all sides of the crucible; the crucible is transferred to a vertical molten salt furnace under an Ar atmosphere for calcination; after cooling to room temperature, the graphite felt is taken out and repeatedly rinsed with deionized water until the molten salt is completely washed away, and then dried in a vacuum drying oven at 80-100°C for later use.

[0053] The calcination conditions include: calcination temperature 200-350°C (NH3HF releases heat during decomposition after 200°C, promoting the decomposition of KClO3, so the calcination temperature does not need to reach 400°C), calcination time 2-3h, heating rate 3-5°C·min -1 (Rapid heating before 200°C, slow heating after 200°C).

[0054] In order to better explain the present scheme, examples are also provided below.

[0055] Implementation Case 1

[0056] Use KF and NaCl to provide a molten salt environment. Both have melting points of 800-900°C and have high thermal stability. KF and NaCl are both analytically pure, with masses of 12g and 8g respectively. KF and NaCl need to be fully mixed and ground for 10 minutes in a dry environment. After KF and NaCl are fully mixed and ground, gradually add 3g of KClO3 (etchant, O source), and stir and mix thoroughly in a dry environment without grinding. Gradually add 1.84g of NH3HF (etchant, N source) in batches to the mixed powder of KF, NaCl and KClO3, stir evenly in a dry environment, and do not grind again. Mix the above

[0057] KF (12g) + NaCl (8g) + KClO3 (3g) + NH3HF (1.84g) etching + N / O doping mixed powder in the crucible is evenly covered with a suitable area of ​​graphite felt on all sides, and the thickness of the upper and lower sides is about 1.5cm. The crucible is transferred to an Ar atmosphere vertical molten salt furnace for calcination at a temperature of 350℃, a calcination time of 3h, and a heating rate of 5℃·min -1 After the end, the crucible was cooled to room temperature, the graphite felt was taken out and repeatedly rinsed with deionized water until the molten salt was completely washed away, and then dried in a vacuum drying oven at 80°C for later use.

[0058] Implementation Case 2

[0059] Use KF and NaCl to provide a molten salt environment. Both have melting points of 800-900°C and have high thermal stability. KF and NaCl are both analytically pure. Take 10g and 10g of them respectively. Mix and grind KF and NaCl thoroughly for 5 minutes in a dry environment. After KF and NaCl are thoroughly mixed and ground, gradually add 0.5g of KClO3 (etchant, O source), and stir and mix thoroughly in a dry environment without grinding. Gradually add 0.2g of NH3HF (etchant, N source) in batches to the mixed powder of KF, NaCl and KClO3, stir evenly in a dry environment, and do not grind again. Mix the above

[0060] KF (10g) + NaCl (10g) + KClO3 (0.5g) + NH3HF (0.2g) etching + N / O doping mixed powder in the crucible is evenly covered with a suitable area of ​​graphite felt on all sides, and the thickness of the upper and lower sides is about 1cm. The crucible is transferred to an Ar atmosphere vertical molten salt furnace for calcination at a temperature of 200℃, a calcination time of 2h, and a heating rate of 3℃·min -1 After the end, the crucible was cooled to room temperature, the graphite felt was taken out and repeatedly rinsed with deionized water until the molten salt was completely washed away, and then dried in a vacuum drying oven at 100°C for later use.

[0061] Implementation case three:

[0062] Use KF and NaCl to provide a molten salt environment. Both have melting points of 800-900°C and have high thermal stability. KF and NaCl are both analytically pure, with masses of 11g and 9g respectively. KF and NaCl need to be fully mixed and ground for 8 minutes in a dry environment. After KF and NaCl are fully mixed and ground, gradually add 1.5g of KClO3 (etchant, O source), and stir and mix thoroughly in a dry environment without grinding. Gradually add 1g of NH3HF (etchant, N source) in batches to the mixed powder of KF, NaCl and KClO3, stir evenly in a dry environment, and do not grind again. Mix the above

[0063] KF (11g) + NaCl (9g) + KClO3 (1.5g) + NH3HF (1g) etching + N / O doping mixed powder in the crucible is evenly covered with graphite felt of appropriate area on all sides, and the thickness of the upper and lower sides is about 1.2cm. The crucible is transferred to an Ar atmosphere vertical molten salt furnace for calcination at 250℃, calcination time 2.5h, and heating rate 4℃·min -1 After the end, the crucible was cooled to room temperature, the graphite felt was taken out and repeatedly rinsed with deionized water until the molten salt was completely washed away, and then dried in a vacuum drying oven at 90°C for later use.

[0064] The graphite felt electrodes in the three embodiments were subjected to charge and discharge tests, and the selected flow battery system was an all-vanadium flow battery. The specific description is as follows: 1. It is composed of the single cell; 2. The battery electrode area is 12cm 2 ; 3. The concentration of vanadium ions in the electrolyte is 1.65 mol / L, and the concentration of sulfate ions is 4.2 mol / L; 4. The current density of the battery constant current charge and discharge is 150 mA / cm 2 ; 5. The charge and discharge cut-off values ​​of the single cell are 1.65V and 1.0V respectively; 6. The volume of the positive / negative electrolyte is 150mL each.

[0065] The experimental results are as follows:

[0066] Figure 2 a, b, and c are microscopic morphology images of GF modified with different process parameters in implementation cases one, two, and three, respectively. The process in implementation case one takes the maximum value of the parameter range of the invention scheme, the process in implementation case two takes the minimum value of the parameter range of the invention scheme, and implementation case three takes the middle value of the parameter range of the invention scheme. By comparison, it is found that the technical invention can etch the surface of graphite felt fiber uniformly to varying degrees. Among them, the fiber surface roughness of implementation case three is greater, and the etching is more obvious. The process of implementation case one takes the maximum value of the parameter range of the invention scheme, which may be because the NH3 generated by the pyrolysis of NH4HF is reducing, and consumes part of the O2 generated from KClO3 at high temperature, thereby slowing down the etching of graphite felt.

[0067] Figure 3 It is the CON element distribution diagram of the surface of unmodified GF (a), (b), (c) and modified GF fiber of implementation case three (d), (e), (f). Compared with the unmodified GF, the N and O element contents on the surface of the modified graphite felt fiber of implementation case three of the present invention are significantly increased.

[0068] Figure 4 The cyclic voltammetry curves of the unmodified GF and the modified GF in Example 3 are shown in Figure 5. Compared with the unmodified GF electrode, the redox peak current of the modified electrode in Example 3 is significantly improved (Ipa: 0.33 mA / cm 2 and Ipc: -0.27mA / cm 2 ; Unmodified graphite felt Ipa: 0.16mA / cm 2 and Ipc: -0.15mA / cm 2 ). This is because the oxygen-containing groups and specific surface area of ​​the modified graphite felt increase, which is VO 2+ / VO 2+ The redox reaction provides more active sites and reaction sites. At the same time, compared with the unmodified GF, the redox peak potential difference (ΔE) of the modified electrode in Example 3 is significantly reduced (ΔE in Example 3: 0.49V; ΔE of unmodified graphite felt: 0.64V), which indicates that the mixed molten salt synchronously modifies the graphite felt electrode with VO 2+ / VO 2+ The electrochemical reversibility of the redox reaction is significantly improved.

[0069] Figure 5 The bar graph of the charge and discharge energy density of unmodified GF and modified GF at different current densities (from left to right, unmodified GF, GF of implementation case 1, GF of implementation case 2, and GF of implementation case 3). The graphite felt electrode modified by synchronous etching + N / O co-doping is used as the positive and negative electrodes of the all-vanadium liquid flow battery. The battery can obtain higher charge and discharge energy efficiency than the unmodified graphite felt electrode at different current densities (unmodified graphite felt electrode 50, 80, 100, 120 and 150 mA / cm 2 The EE under different current densities are 81.2%, 80.1%, 79.4%, 78.5% and 77.2% respectively), which is due to the high reversibility, high specific surface area and high activity of the modified electrode of the present invention. At the same time, the energy efficiency of the modified electrode of Example 3 under different current densities is higher than that of the modified graphite felt electrodes of Examples 1 and 2 (50, 80, 100, 120 and 150 mA / cm for the modified graphite felt electrode of Example 3). 2 The EE under the above conditions are 85.7%, 84.8%, 83.5%, 83.2% and 82.8% respectively. The reasons are the same as Figure 1 analyze.

[0070] Figure 6 Figure 3 is the charge and discharge voltage curve of the unmodified GF and the modified GF in Example 3. The modified graphite felt electrode in Example 3 has a larger specific surface area, higher conductivity and higher redox activity, thus showing a lower charge voltage to the charge cut-off voltage of 1.60V and a higher discharge voltage thereafter, indicating that the redox process of the modified electrode in Example 3 has a smaller polarization overpotential.

[0071] The present invention also provides a device for modifying graphite felt electrodes of liquid flow batteries, comprising: a first obtaining unit, used to fully mix and grind initial powders in a dry environment to obtain a first mixed powder; a second obtaining unit, used to add reagents providing an oxygen source to the first mixed powder in batches, and obtain a second mixed powder by stirring in a dry environment; a third obtaining unit, used to add reagents providing a nitrogen source to the second mixed powder in batches, and obtain a third mixed powder by stirring in a dry environment; and a calcination unit, used to cover the graphite felt electrode with the third mixed powder for calcination modification.

[0072] Since the content protected by this device is similar to that protected by the above method, no further introduction will be given here. Please refer to the discussion section of the above method for details.

[0073] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for modifying a graphite felt electrode of a flow battery, characterized in that: include: Fully mixing and grinding the initial powders in a dry environment to obtain a first mixed powder; Adding a reagent providing an oxygen source to the first mixed powder in batches, and obtaining a second mixed powder by stirring in a dry environment; Adding a nitrogen source providing reagent to the second mixed powder in batches, and obtaining a third mixed powder by stirring under a dry environment; Covering the graphite felt electrode with the third mixed powder for calcination modification; The initial powder includes at least two of the following: KF, NaCl, KCl, NaF, KBr and NaBr.

2. The method according to claim 1, characterized in that The initial powders are KF and NaCl; wherein the mass ratio of the KF to the NaCl is 1:1 to 1.5:

1.

3. The method according to claim 1, characterized in that The mixing and grinding time is 5-10 minutes.

4. The method according to claim 2, characterized in that: The reagent providing an oxygen source comprises at least one of the following: KClO4, KClO3, KClO2, KBrO3, KBrO2, NaClO4, NaClO3, NaClO2, NaBrO3 and NaBrO; The reagent providing the nitrogen source includes at least one of the following: NH3HF, NH4Cl and NH4Br.

5. The method according to claim 4, characterized in that The reagent providing the oxygen source is KClO3; wherein the mass of the KClO3 added is 2-15% of the total mass of the KF and the NaCl.

6. The method according to claim 4, characterized in that The reagent providing the nitrogen source is NH3HF; wherein the mass of the added NH3HF is 0.8-8% of the total mass of the KF, the NaCl and the KClO3.

7. The method according to claim 1, characterized in that The third mixed powder is used to cover the graphite felt electrode for calcination modification, comprising: Placing a graphite felt electrode in a crucible, and evenly covering the third mixed powder with the graphite felt on all sides; The crucible is transferred to a vertical molten salt furnace under an Ar atmosphere for calcination; Wherein, the thickness of the covering is 1-1.5 cm.

8. The method according to claim 6, characterized in that The calcination conditions include: calcination temperature 200-350°C, calcination time 2-3h, heating rate 3-5°C 5min -1 .

9. The method according to claim 1, characterized in that: The method further comprises: The modified graphite felt electrode was removed from the crucible and rinsed repeatedly with deionized water; The rinsed graphite felt electrode was placed in a vacuum drying oven for drying.

10. A device for modifying graphite felt electrodes of a flow battery, characterized in that: include: A first obtaining unit is used to fully mix and grind the initial powder in a dry environment to obtain a first mixed powder; A second obtaining unit is used to add a reagent providing an oxygen source to the first mixed powder in batches, and obtain a second mixed powder by stirring in a dry environment; A third obtaining unit is used to add a reagent providing a nitrogen source to the second mixed powder in batches, and obtain a third mixed powder by stirring in a dry environment; A calcination unit is used for calcining and modifying the graphite felt electrode by covering it with the third mixed powder.

Citation Information

Cited By

  • Modified graphite felt electrode for all-vanadium redox flow battery and preparation method of modified graphite felt electrode

    CN120809843A